THE INFLUENCE OF NURSE WORKLOAD AND MOTIVATION ON PATIENT SAFETY WITH KNOWLEDGE AS A MEDIATION VARIABLE IN TANGERANG CITY HOSPITAL - Evy Herawati; Eka Desy Purnama; Wani Devita Gunardi (RADJA PUBLIKA, 2023)
This study aims to determine how much influence the workload and motivation of nurses have on patient safety in Tangerang City Hospital. The number of samples in this study were 100 respondents. The data used is a type of quantitative data obtained from filling out questionnaires by selected respondents through simple random sampling. The analytical method used in this research is through the Structural Equation Model (SEM) approach using the Smart PLS program. The results of this study indicate that there is a significant effect of workload and nurse motivation on patient safety with knowledge as a mediating variable in Tangerang City General Hospital. The population of the study is limited to the Tangerang Regional Hospital. Further research is expected to be carried out in other locations so that a comparison of findings in studies related to patient safety can be carried out.